Il ruolo della conoscenza nell’adozione di innovazioni di processo nelle micro imprese - D’andrea, Dajana; Ceci, Federica (Piccola Impresa / Small Business, 2009)
Mechanization of production processes allows the achievement of important advantages,especially in terms of increase in production volumes and decrease in production costs.Despite of these advantages, many micro and small companies are still adopting manualproduction. Causes can be searched in the characteristics of the production process itself thatcan make the mechanization difficult. This paper aims to investigate if the decision aboutthe mechanization is influenced by the characteristics of the knowledge underpinning theproduction. On the basis of empirical evidences collected in micro and small companiesoperating in the diary sector, we discuss how the knowledge tacit dimension influencesthe mechanization of the production process, the diffusion and transfer of productioncapabilities in a given territory.